The invasion of five alien species in the Delta do Parnaíba Environmental Protection Area, Northeastern Brazil - Loebmann, Daniel [UNESP]; Mai, Ana Cecília G.; Lee, James T. (My University, 2010)
Marine biological invasions have been regarded as one of the major causes of native biodiversity loss, with shipping and aquaculture being the leading contributors for the introductions of alien species in aquatic ecosystems. In the present study, five aquatic alien species (one mollusk, three crustaceans and one fish species) were detected during dives, shore searches and from the fisheries on the coast of the Delta do Parnaíba Environmental Protection Area, in the States of Piauí and Maranhão, Northeastern Brazil. The species were the bicolor purse-oyster Isognomon bicolor, the whiteleg shrimp Litopenaeus vannamei, the giant river prawn Macrobrachium rosenbergii, the Indo-Pacific swimming crab Charybdis hellerii and, the muzzled blenny Omobranchus punctatus. Ballast water (I. bicolor, C. hellerii, and O. punctatus) and aquaculture activities (L. vannamei and M. rosenbergii) in adjacent areas are the most likely vectors of introduction. All exotic species found have potential impact risks to the environment because they are able to compete against native species for resources (food and habitat). Isognomon bicolor share the same habitat and food items with the native bivalve species of mussels and barnacles. Litopenaeus vannamei share the same habitat and food items with the native penaeids such as the pinkspot shrimp Farfantepenaeus brasiliensis, the Southern brown shrimp Farfantepenaeus subtilis, and the Southern white shrimp Litopenaeus schmitti, and in the past few years L. vannamei was responsible for a viral epidemics in the cultivation tanks that could be transmitted to native penaeid shrimps. Charybdis hellerii is also able to cause impacts on the local fisheries as the species can decrease the populations of native portunid crabs which are commercialized in the studied region. Macrobrachium rosenbergii may be sharing natural resources with the Amazon River prawn Macrobrachium amazonicum. Omobranchus punctatus shares habit with the native redlip blenny Ophioblennius atlanticus and other fishes, such as the frillfin goby Bathigobius soporator. Some immediate remedial measures to prevent further introductions from ballast water and shrimp farm ponds should be: (i) to prevent the release of ballast water by ship/vessels in the region; (ii) to reroute all effluent waters from shrimp rearing facilities through an underground or above-ground dry well; (iii) to install adequate sand and gravel filter which will allow passage of water but not livestock; (iv) outdoor shrimp pounds located on floodable land should be diked, and; (v) to promote environmental awareness of those directly involved with ballast water (crews of ship/vessels) and shrimp farms in the region.
Keywords: Aquaculture; Ballast water; Blenniidae; Decapoda; Exotic species; Mollusca